Strengthening Digital Literacy and MSMEs Marketing Innovation in Supporting the Sustainability of Local Businesses in Purwokerto - Sev Rahmiyanti; Wiwiek Rabiatul Adawiyah; Christina Tri Setyorini (Jurnal Pengabdian UNDIKMA, 2026)
This community service activity aims to enhance the digital literacy capacity and marketing innovation of micro, small, and medium enterprises (MSMEs) in supporting the sustainability of local businesses in Bobosan Village, North Purwokerto District, Banyumas Regency. The program was initiated in response to the low level of digital literacy among MSME actors, limited use of social media and marketplace platforms, and a lack of innovation in marketing strategies, all of which have constrained market reach and business competitiveness. The implementation methods included digital literacy training, digital marketing strategy workshops, assistance in the use of social media and marketplaces, and simulations of digital content creation, conducted in stages ranging from needs identification to monitoring and evaluation. Evaluation instruments included pre-test and post-test questionnaires, observation sheets, and participant feedback forms to assess changes in knowledge, skills, and attitudes. The data were analyzed using descriptive quantitative techniques by comparing participants’ conditions before and after the program. The results showed measurable improvements among participants, with understanding of digital marketing increasing by approximately 35%, ability to use digital platforms by 30%, and skills in creating digital content by 25%. Participants also began implementing digital marketing strategies in their businesses. In addition, partners responded positively to the program, stating that the materials were easy to understand, the activities were beneficial, and their digital knowledge and skills had improved. This activity was further supported by participants’ enthusiasm, internet access, and practical learning materials, although challenges remained in the form of limited technological capabilities and implementation time. Overall, the findings indicate that the community service program effectively enhanced the digital literacy capacity and marketing innovation of MSMEs while encouraging the adoption of digital marketing to support the sustainability of local businesses.